Assessing sustainability of green supply chain performance: The roles of agile innovative products, business intelligence readiness, innovative supply chain process integration, and lean supply chain capability as a mediating factor - AL-Shboul, Moh’d Anwer (Journal of open innovation, 2025)
This study aims to investigate the impact of business intelligence readiness (BIR), innovative supply chain process integration (ISCPI), and agile innovative products (AIPs) on the sustainability of green supply chain performance (SGSCP) in manufacturing companies (MFs) in growing Middle Eastern nations. The lean supply chain capability (LSCC) role is also investigated as a mediating component. 113 possible self-administrated surveys were evaluated using a quantitative approach through structural equation-modeling (i.e., Smart-PLS application). The study's sample unit consists of all middle- and senior-level managers working for Middle Eastern financial firms. In addition to bootstrapping, convergent and discriminant validity tests were carried out. LSCC was one of the mediating variables we used. The study's findings support the idea, which showed a notable improvement in the link between BIR, ISCPI, AIPs, and SGSCP. The results also showed that the mediating component, or LSCC, had a favorable and substantial impact on SGSCP, validating and supporting the idea that the mediating factor represented by LSCC had a major impact. This study improved the proposed conceptual research model and included a few more components, including AIPs, BIR, ISCPI, LSCC, and SGSCP. For managers, practitioners, and decision-makers in the Middle Eastern MF nations, this study provided fresh and insightful data and insights that served as a roadmap and barometer of how crucial it is to use these aspects in their operations to boost their firms' competitive advantages. It also plugs the knowledge gap and expands the body of prior research by addressing a void in the SCM literature.